The Use of the American Society of Anesthesiologists (ASA) Classification System in Evaluating Outcomes and Charges Following Deformity Spine Procedures. (16th November 2020) - Baron, Rebecca; Shuman, William; Neifert, Sean N; Chapman, Emily K; Gilligan, Jeffrey; Schupper, Alexander J; Gal, Jonathan; Caridi, John M
Abstract: INTRODUCTION: Adult spinal deformity (ASD) has increased prevalence in elderly populations. Due to the high cost of these procedures, several studies have evaluated risk factors that lead to readmissions and poor outcomes. The American Society of Anesthesiologists (ASA) classification system has been applied to patients with ASD in order to assess preoperative health and assess the correlation between ASA class and postoperative complications. METHODS: Patients undergoing spine deformity procedures at a single institution between 2008–2016 were included in this study and subsequently divided into cohorts based on ASA status. Primary outcomes included patient demographics, adjusted LOS, and cost of care. Secondary measures included delayed extubation, ICU stay, in-hospital complications, reoperation rates, non-home discharge, and readmission rates were compared between cohorts. RESULTS: A total of 543 patients diagnosed with ASD were included in this study. Higher ASA class was correlated with greater Elixhauser Comorbidity Index (ECI) scores ( P < .0001) and older age ( P < .0001). Univariate analysis showed longer LOS ( P < .0001) and greater direct costs in patients with higher ASA class ( P < .0001). Patients in ASA Class IV had the greatest rates of ICU stay (80%) when compared to other groups ( P < .0001). Upon multivariable linear regression analysis, only length of stay was statistically significant for ASA class IV versus class I patients (regression estimate = 11.5, CI 6.1-17.0). Furthermore, direct costs were greater for ASA class IV vs. I (regression estimate = +15, 086, P = .021). CONCLUSION: This study demonstrates that ASA class is correlated with greater rates of non-home discharge, total direct costs, and longer length of stay in spine deformity patients.